Comments on Some Axioms for Combining Expert Judgments - Schervish, Mark J. (Management Science, 1986)
Morris (Morris, P. A. 1983. An axiomatic approach to expert resolution. Management Sci. 29 24–32.) develops an axiom system for combining expert judgments by means of a processing rule. It is shown that the axioms are self-contradictory.